The Current Zimbabwean Liquidity Crisis: A Review of its Precipitates - Dlamini, Banele; Mbira, Leonard (Journal of Economics and Behavioral Studies, 2017)
The liquidity crisis has beleaguered banks and has been bedeviling companies since 2009, after the introduction of the multi-currency system which has affected the Zimbabwean economic development. This research paper aims at investigating the causes of the liquidity crisis faced in the Zimbabwean economy. The study used survey design and researcher administered questionnaires in collecting data from the respondents located in Harare, Bulawayo, Gweru and Masvingo. Out of the 200 questionnaires issued, 150 were successfully completed and returned resulting in a response rate of 75%. The study also used secondary data obtained from government agencies on export and import performance. SPSS AMOS was used to test the hypothesis raised and generate a path model determining the size and strength of the direct and indirect influence between the predictor variables and the downstream variable. The study identifies the following antecedents of liquidity crisis; public and investor confidence, country risk, and externalization of funds, illicit financial flows, and net export performance as significant drivers that have an effect on the current liquidity crisis. The results showed that the absence of the lender of last resort role by the central bank has no significant contribution to the liquidity crisis currently obtaining. It is recommended that the government focuses on the aforementioned antecedents in order to address the liquidity crisis.